A New Paradigm: Exploring the Effects of PBL and Other Pedagogical Methods on Freshman Engineering Learning Outcomes - Umamaheswara Singh, R. (Journal of Engineering Education Transformations, 2025)
Context This paper explores the implementation of project-based learning (PjBL) within a freshman engineering applied physics course. PjBL offers a dynamic approach, engaging students in real-world problem-solving scenarios that enhance their understanding of theoretical concepts. With a growing emphasis on experiential learning in STEM education, this study investigates the efficacy of PjBL in fostering both conceptual understanding and practical skills among freshman engineering students. While existing research suggests PjBL promotes deeper learning outcomes and better retention, further exploration within the context of applied physics is warranted. Purpose This study investigates the comparative effects of project-based learning (PjBL) and traditional lecture-based instruction on student learning outcomes in a freshman engineering applied physics course. The hypothesis is that PjBL will lead to superior learning outcomes compared to traditional instruction and other conventional methods. This study aims to gain insights into the potential benefits of adopting PjBL in engineering education and its implications for enhancing student success in applied physics courses. Approach Sixty-three students enrolled in a freshman engineering applied physics course participated in this study. Students experienced a variety of pedagogical methods, including PjBL. PjBL activities promoted active engagement, problem-solving skills (abilities to apply theoretical knowledge in structured scenarios and adapt to complex situations), and real-world application of theoretical concepts. Pre- and post-assessment tests measured baseline knowledge and learning outcomes, while student feedback surveys assessed perceptions of learning experiences, engagement levels, and satisfaction with the teaching methods. Results Quantitative data from pre- and post-assessment scores were analyzed to identify significant differences in learning gains across pedagogical methods. Qualitative data from student surveys were analyzed thematically to uncover common perceptions and experiences. Post-implementation assessments revealed higher levels of conceptual understanding, problem-solving proficiency, and critical thinking skills among students engaged in PjBL activities compared to those in traditional lecture-based instruction. Conclusion The implementation of PjBL in the freshman engineering applied physics course led to significant improvements in student learning outcomes. Post-implementation assessments revealed higher levels of conceptual understanding, problem-solving proficiency, and critical thinking skills among students who engaged in PjBL activities compared to those who experienced traditional lecture-based instruction. These findings align with existing research suggesting that PjBL enhances student engagement, promotes deeper learning, and better prepares students for real-world applications in STEM education.